Change of Quadriceps Muscular Strength and Muscle Activity According to Knee Extension Angle and Body Mass Index (Medico Legal Update, 2019)
The purpose of this study was to investigate the effect of body mass index (BMI) on muscle strength andactivity according to the knee angle. Muscle activity of vastus medialis (VM), vastus lateralis (VL), and rectusfemoris (RF) was measured for 48 healthy adults. Isokinetic equipment was used to measure the isometricstrength of the knee extensors at 0°, 30°, 60°, and 90° flexion. One-way ANOVA was used to compareisometric muscle strength and activity. The maximum isometric strength of the knee extensors accordingto the knee angle showed a significant difference between the groups at 0°, 30°, and 90° of knee flexion(p